Handbook of fluidization and fluid-particle systems - Yang, Wen-ching, 1939- (Chemical industries ;, 2003)
Particle characterization and dynamics. Yang, Wen-Ching - Flow through fixed beds. Yang, Wen-Ching - Bubbling fluidized beds. Yang, Wen-Ching - Elutriaton and entrainment. Werther, Joachim; Hartge, Ernst-Ulrich - Effect of temperatre and pressure. Yates, J. G. - Gas distributor and plenum design in fluidized beds. Reddy Karri, S. B.; Werther, Joachim - Effect of internal tubes and baffles. Jin, Yong; Wei, Fei; Wang, Yao - Attrition. Werther, Joachim; Reppenhagen, Jens - Modeling. Ho, Thomas C. - Heat transfer. Chen, John C. -Mass transfer. Ho, Thomas C. - General approaches to reactor design. Jiang, Peijun ; Wei, Fei; Fan, Liang-Shih - Fluidized bed scaleup. Glicksman, Leon R. - Applications for fluid catalytic cracking. Chen, Ye-Mon - Applications for gasifiers and combustors. Newby, Richard A. - Applications for chemical production and procesing. Jazayeri, Behzad - Applications for coating and granulation. Tardos, Gabriel I.; Mort, Paul R. - Applications for fluidized bed drying. Mujumdar, Arun S.; Devahastin, Sakamon - Circulating fluidized beds. Grace, John R.; Bi, Hsiaotao; Golriz, Mohammad - Other nonconventional fluidized bed. Yang, Wen-Ching - Standpipes and nomechanical valves. Knowlton, T. M.; Cyclone separators. Knowlton, T. M.; Dilute-phase pneumatic conveyin. Klinzing, George E.; Electrostatics in pneumatic conveying. Klinzing, George E. - Instrumentation and measurements. Horio, Masayuki; Kobylecki, Rafal P.; Tsukada, Mayumi - Liquid-solids fluidization. Epstein, Norman - Gas-liquid-solid three-phase fluidization. Fan, Liang-Shih; Yang, Guoqiang - Liquid-solids separation. Chiang, Shiao-Hung; He, Daxin; Feng, Yuru.